Masyarakat dan Kebudayaan Sekolah - Normina Normina (UIN Antasari Banjarmasin, 2015)
Humans are born already has a herd instinct to live, so he called a social animal. As a social animal instinct that humans have called gregariousness, the relationship between man and his fellow. Culture affects individuals in different ways but the individual also affects the culture resulting in social change. From birth to death man lives as members of society. Culture school education system to develop certain patterns of behavior in accordance with what is expected by the public and students. Life in the schools as well as the norms prevailing in situ can be called Culture School. In the school there are some elements of culture are broadly as follows: Location of environment and physical infrastructure of schools, school curriculum, Persons values norms, regulatory systems, and climate school life. Meanwhile, according to Hedley Beare First, elements that are not visible matadan second element is visible